ANTi-History : theorization, application, critique and dispersion - Deal, Nicholous M.; Hartt, Christopher M.; Mills, Albert J. (Emerald Publishing Limited, 2023)
There has been a surge of ANTi-History research over the last 15 years. ANTi-History brings together the most impactful efforts to develop, apply and critique ANTi-History in one comprehensive book. Deal, Hartt and Mills make sense of and organize the ongoing conversation around ANTi-History, using it as a lens to assess both the future and the potential of the budding field of historical organization studies and business history. They offer a systematic close reading of ANTi-History through its introduction to the field nearly two decades ago; the literatures that theorize it as an approach for 'doing history' and how others have contributed to its usefulness to scholars, practitioners, and students. In addition, they offer an exploration of the empirical research areas, settings, and contexts - especially its position within an archival zeitgeist in critical management studies - that scholars have engaged in; and the international character that it has taken across numerous countries around the world. ANTi-History revisits the debates that concern ANTi-History and its theorization of the past, identifying potential future research and unique opportunities to further advance and refine ANTi-History and critical historiography scholarship.
Includes index.
Keywords: Historiography.; History, Historiography.; elektronické knihy; electronic books